Correction: Phonetic differences between affirmative and feedback head nods in German Sign Language (DGS): A pose estimation study. - Anastasia Bauer; Anna Kuder; Marc Schulder; Job Schepens (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0304040.].